Ostati ali oditi - doživljanja mednarodnih študentov v času epidemije bolezni covid-19 - Milavec Kapun, Marija (Družboslovne razprave, 2020)
Slovenia has recognized student mobility as a key strategic goal of higher education development. This opens up opportunities for progress but also creates challenges that were highlighted during the Covid-19 epidemic. During this crisis, international students in Slovenia were faced with the decision whether to stay or return home. The reasons why they chose to remain/depart were determined by analysing the content of the answers to the open-ended question. Students mainly stayed for personal and health reasons, because of the epidemic, the accompanying measures and the pedagogical process. The reasons for leaving mainly featured psychosocial factors, the epidemic and related measures, personal reasons and access to healthcare. Due to psychosocial distress, international students experienced a great need during the epidemic for targgeted support measures and especially for coordinated and accessible information
Keywords: coronavirus; covid-19; distress; Erasmus+; health; higher education; isolation; izolacija; mednarodne izmenjave; pandemic isolation; pandemija; stiska; study abroad; študentje na izmenjavi; tuji študentje; visoko šolstvo; zdravje